Self-Regulated Writing Strategy Use When Revising Upon Automated, Peer, and Teacher Feedback in an Online English as a Foreign Language Writing Course - Tian, Lili; Liu, Qisheng; Zhang, Xingxing (Frontiers in Psychology, 2022)
Research investigating the intricacies of how self-regulated writing strategies are used in a finely focused area of the L2 writing process is still lacking. This study takes a mixed-methods approach to explore Chinese EFL learners’ use of self-regulated writing strategies when revising based on automated, peer, and teacher feedback in an online EFL writing context. Thirty-six Chinese university learners filled in three questionnaires (one per feedback source). Additionally, four learners of them followed a think-aloud protocol while revising and responded to a stimulated recall interview to provide further data. The results revealed that learners employed an array of self-regulated writing strategies to attain their feedback -revision goals. Learners used more cognitive strategies when revising based on automated feedback than compared to peer and teacher feedback, and more motivational strategies when revising based on teacher feedback than automated and peer feedback. The think-aloud protocols data and stimulated recall interviews coincided with the quantitative findings. Textual analysis revealed that feedback type and quantity were associated with self-regulated writing strategy use.